2014
DOI: 10.1039/c3cc48877b
|View full text |Cite
|
Sign up to set email alerts
|

Transparent p-type epitaxial thin films of nickel oxide

Abstract: Transparent p-type nickel oxide (NiO) thin films have been epitaxially grown on (0001) Al2O3 substrates by a chemical solution method of polymer-assisted deposition for the first time. The films have a high optical transparency of above 95% in the wavelength range of 350-900 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…They have been also studied as hydrogen and other gas sen sor materials (6), thin film transistors (7) and capacitors (8). As a promising candidate of p-type transparent conducting films (9). nickel oxide thin films have been investigated as hale-transport interlayers in optoelectronic devices (10) and thin film diodes (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been also studied as hydrogen and other gas sen sor materials (6), thin film transistors (7) and capacitors (8). As a promising candidate of p-type transparent conducting films (9). nickel oxide thin films have been investigated as hale-transport interlayers in optoelectronic devices (10) and thin film diodes (11).…”
Section: Introductionmentioning
confidence: 99%
“…ln this work, we have been interested in non-stoichiometric nickel oxide (Ni 1 _xO) thin films with two potential applications motivation: anodic coloration layers in electrochromic devices [18.19) and p-type transparent conductive films [9). ln both of the two applications oriented properties and performances, preparation methods and deposition conditions, microstructures of the films, electrical and optical properties are all critical influential factors and closely correlated to those performances.…”
Section: Introductionmentioning
confidence: 99%
“…The PAD processes utilised by Jia et al allowed for a single layer epitaxial deposition of SrTiO 3 on LaAlO 3 with a dielectric constant greater than 200 and a loss of <1% at 1 MHz which is comparable to thin film dielectrics deposited using pulsed laser deposition . The use of PAD techniques has improved considerably in recent times, with many studies showing the efficacy of PAD techniques particularly in the preparation of epitaxial metal oxide growth with the underlying substrate . The PAD technique increases the scope of the solution processed depositions allowing for an increased range of materials and stoichiometric surfaces to be prepared.…”
Section: Deposition Techniquesmentioning
confidence: 99%
“…It has been found that the electron and ion transport efficiency for charge storage in pseudocapacitors depends on the electrode properties such as the surface morphology and surface area of NiO. NiO is a potential material used as an antiferromagnetic layer [25], p-type transparent conducting films [26] in electrochromic devices [27] and as a functional sensor layer for chemical sensing [28]. Different methods have been used to deposit thin films of NiO such as chemical bath deposition [10], SILAR [29], spray pyrolysis [30], radio frequency magnetron sputtering [31], chemical vapour deposition [32], sol-gel [33] and electrochemical deposition methods [34].…”
Section: Introductionmentioning
confidence: 99%